2010
DOI: 10.1021/nn901853e
|View full text |Cite
|
Sign up to set email alerts
|

Block Copolymer Nanocontainers

Abstract: Using cell dynamics computer simulation, we perform a systematic study of thin block copolymer films around a nanoparticle. Lamellar-, cylinder-, and sphere-forming block copolymers are investigated with respect to different film thicknesses, particle radii, and boundary conditions at the film interfaces. The obtained structures include standing lamellae and cylinders, "onions", cylinder "knitting balls", "golf ball", layered spherical, "virus"-like and mixed morphologies with T-junctions and U-type defects. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
60
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(66 citation statements)
references
References 74 publications
(146 reference statements)
5
60
0
1
Order By: Relevance
“…Compared to the DLS sample, dehydration and subsequent collapse of the polymer chain for TEM sample could lead to a smaller diameter. Similar difference in size as a result of different measuring techniques was also made in other papers [25][26][27]. The electronic absorption and basic photophysical properties for SPPLGA were characterized in DMF by UV-vis spectroscopy (Fig.…”
Section: Self-assembly Behavior Of Spplgasupporting
confidence: 68%
“…Compared to the DLS sample, dehydration and subsequent collapse of the polymer chain for TEM sample could lead to a smaller diameter. Similar difference in size as a result of different measuring techniques was also made in other papers [25][26][27]. The electronic absorption and basic photophysical properties for SPPLGA were characterized in DMF by UV-vis spectroscopy (Fig.…”
Section: Self-assembly Behavior Of Spplgasupporting
confidence: 68%
“…Polymersomes can also be designed to behave in a similar way, starting from copolymers with blocks that have stimulus-dependent solubility and that can lead to the disintegration of the polymersome or to the creation of pores in the layers when the stimulus appears (Figure 18.7) [132,140]. Furthermore, the morphology of the micelles and polymersomes could be tailored to obtain novel nanostructures, including cylinders, ''onions,'' ''knitting ball,'' ''golf ball,'' or ''virus''-like particles, not explored yet as drug carriers [141].…”
Section: Self-assembled Polymers: Micelles and Polymersomesmentioning
confidence: 99%
“…which will contribute to polymer motion as prescribed in Equation 6. As opposed to previous approaches, [16][17][18] we describe individual colloids through a soft interaction.…”
Section: Colloid Dynamicsmentioning
confidence: 99%
“…Previous studies have shown that this assumption can lead to experimental relevant results. [5,6] Since the polymer is treated in terms of its local monomer concentration we introduce a free energy functional which will provide…”
Section: Introductionmentioning
confidence: 99%